2014
DOI: 10.1155/2014/135212
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Effects of Acupuncture and Moxibustion by Hyperspectral Imaging Technique

Abstract: This study was to observe the effects of acupuncture and moxibustion on spectrum features of acupoint using hyperspectral imaging (HSI) technique. HSI of the Neiguan (PC6) in the acupuncture groups, moxibustion groups, and control groups was scanned by the hyperspectral imager to analyze the spectrum features and the variations within the wavelength of 400–1000 nm and explore the relationship between the spectral characteristics and effects of acupuncture and moxibustion. The light absorption intensity was sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…of local tissue and function of the skin tissue structure (texture, sweat gland, and sebaceous gland). And the effect of moxibustion was more obvious [ 35 ]. In this study, it was found that the temperature, BP, and SaO 2 of acupoints obviously increased after MS moxibustion too.…”
Section: Discussionmentioning
confidence: 99%
“…of local tissue and function of the skin tissue structure (texture, sweat gland, and sebaceous gland). And the effect of moxibustion was more obvious [ 35 ]. In this study, it was found that the temperature, BP, and SaO 2 of acupoints obviously increased after MS moxibustion too.…”
Section: Discussionmentioning
confidence: 99%